PENGGUNAAN BUKU DIGITAL UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN DENGAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) DI KOBER FAJAR MULIA - Damayanti, May; Hizriyani, Rina; Maulana, M. Azka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language development is a fundamental aspect of early childhood development. Preliminary observations at Kober Fajar Mulia indicated that the language skills of children aged 4-5 years were still at the Beginning to Develop level, highlighting the need for innovative learning approaches to optimally stimulate language development. This study aimed to examine the effect of using digital books integrated with the Structural Analytic Synthetic (SAS) method on the language skills of children aged 4-5 years. A quantitative approach with a quasi-experimental method and a pretest-posttest control group design was employed. The participants consisted of 20 children divided into an experimental group and a control group. Data were collected using a validated and reliable observation sheet and analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, N-Gain analysis, and the Independent Samples t-test. The results showed that the experimental group achieved an N-Gain score of 0.601 (moderate category), while the control group obtained an N-Gain score of 0.037 (low category). The Independent Samples t-test yielded a significance value of p < 0.001, indicating a statistically significant difference between the two groups. Therefore, the use of digital books integrated with the Structural Analytic Synthetic (SAS) method significantly improved the language skills of children aged 4-5 years.